2013
DOI: 10.1371/journal.pone.0063226
|View full text |Cite
|
Sign up to set email alerts
|

Gli1 Mediates Lung Cancer Cell Proliferation and Sonic Hedgehog-Dependent Mesenchymal Cell Activation

Abstract: Non-Small-Cell-Lung-Cancer (NSCLC) represents approximately 85% of all lung cancers and remains poorly understood. While signaling pathways operative during organ development, including Sonic Hedgehog (Shh) and associated Gli transcription factors (Gli1-3), have recently been found to be reactivated in NSCLC, their functional role remains unclear. Here, we hypothesized that Shh/Gli1-3 could mediate NSCLC autonomous proliferation and epithelial/stromal signaling in the tumoral tissue. In this context, we have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 53 publications
(68 reference statements)
6
70
0
Order By: Relevance
“…Oncogenic KRas or Egfr were shown to cooperate with dominant active Gli2 activation in a mouse model of pancreatic ductal adenocarcinoma (59). In human non-small cell lung cancer cell lines, knockdown of Gli1 and Gli2 affects proliferation, migration, and invasion (60). Moreover, TCGA data analysis of lung adenocarcinoma patients showed that GLI1 and KRAS copy number alterations coexist in a subset of patients (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Oncogenic KRas or Egfr were shown to cooperate with dominant active Gli2 activation in a mouse model of pancreatic ductal adenocarcinoma (59). In human non-small cell lung cancer cell lines, knockdown of Gli1 and Gli2 affects proliferation, migration, and invasion (60). Moreover, TCGA data analysis of lung adenocarcinoma patients showed that GLI1 and KRAS copy number alterations coexist in a subset of patients (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Together, these data show that Hh-related molecules are highly expressed in IPF lungs, indicating an activation of the Hh pathway in this type of lung fibrosis. Moreover, in fibroblasts, Shh increases the synthesis of proteins related to ECM, such as collagen and fibronectin [112,113]. Interestingly, inhibition of the Hh pathway reduces the expression of a-SMA, collagen 1 and fibronectin and abrogates the effect of TGF-b on these proteins [111], highlighting the importance of the TGF-b/Hh crosstalk that may promote a mesenchymal phenotype in pathological contexts.…”
Section: Hedgehog Signallingmentioning
confidence: 99%
“…Interestingly, inhibition of the Hh pathway reduces the expression of a-SMA, collagen 1 and fibronectin and abrogates the effect of TGF-b on these proteins [111], highlighting the importance of the TGF-b/Hh crosstalk that may promote a mesenchymal phenotype in pathological contexts. In different types of lung cancer, the Shh pathway has also been found to be re-activated [99,[113][114][115][116], and is involved in the mesenchymal transition of tumoural cells associated with the formation of metastases. In a model of lung metastases, colon carcinoma cells injected into nude mice induced pulmonary lesions.…”
Section: Hedgehog Signallingmentioning
confidence: 99%
“…In the co-culture experiments, we used VXN2 (passage number [10][11][12][13][14][15][16][17][18][19] and TF (passage number 3-12) cells. After harvesting the cells from tissue cultures flasks, we labeled the VXN2 cells by cell tracker green.…”
Section: Supporting Informationmentioning
confidence: 99%
“…[15] We suggest that this behavior could, in part, be due to the activity of the transforming growth factor-beta (TGF-beta)…”
mentioning
confidence: 99%